Liquid crystal display backlight module and preparation method thereof

CN122902131APending Publication Date: 2026-10-13SHENZHEN GOODSTAR TECH CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611306484.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-08-26
Publication Date
2026-10-13

AI Technical Summary

Technical Problem

[0007]针对现有背光模块导光板存在应力翘曲,影响出光均匀性的问题,本发明提供一种液晶显示屏背光模组及其制备方法

Benefits of technology

[0018]根据本发明提供的液晶显示屏背光模组,采用了丙烯酸酯交联共聚物作为导光板材料,丙烯酸酯交联共聚物包括甲基丙烯酸甲酯单元、金刚烷丙烯酸酯单元、硅氧烷丙烯酸酯单元和聚醚链段,其中,甲基丙烯酸甲酯单元提供基础的高透光性与加工性能;聚醚链段的C-O-C醚键内旋转位垒低,在-40~85℃的服役区间内始终处于高弹态;激光打点时,表层瞬间高温膨胀产生压应力、内部受拉产生拉应力,聚醚链段可通过快速构象舒展/卷曲缓冲局部形变差,冷却过程中缓慢释放应力,使网点区域残余应力降低50%以上,从本质上缓解表面压应力与内部拉应力的不平衡状态。硅氧烷丙烯酸酯单元一方面通过双键共聚接入主链,另一方面通过水解缩合同时实现分子间交联与聚乙二醇共价接枝,既保证聚醚链段不迁移、不析出,长期稳定性远优于物理共混体系;又通过轻度交联网络限制分子链永久滑移,避免引入柔性链后出现高温蠕变增大的副作用。而金刚烷丙烯酸酯单元的笼型脂环结构产生强空间位阻,将材料玻璃化转变温度提升至120℃以上,可以克服由于聚醚链段导致的材料玻璃化转变温度下降的问题,同时压缩分子自由体积,使本征线热膨胀系数降低30%以上,从根源上减小热变形驱动力。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure FT_1
    Figure FT_1
  • Figure FT_2
    Figure FT_2
  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

In order to overcome the problem that the light guide plate of the existing backlight module has stress warping and affects the light uniformity, the application provides a backlight module of a liquid crystal display screen, which comprises a side-in light source, a light guide plate and a reflection layer, the side-in light source is located at the side of the light guide plate and faces the light guide plate, the light guide plate has a light emitting surface and a backlight surface, the reflection layer is located on the backlight surface of the light guide plate, the backlight surface of the light guide plate is provided with scattering points formed by laser dotting, the light guide plate is an acrylate cross-linked copolymer, the acrylate cross-linked copolymer comprises an acrylate main chain and a polyether chain segment, the acrylate main chain comprises methyl methacrylate units, adamantane acrylate units and siloxane acrylate units, and the two ends of the polyether chain segment are covalently connected between different siloxane acrylate units.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the technical field of liquid crystal display backlight module materials, specifically relating to a liquid crystal display backlight module and its preparation method. Background Technology

[0002] Liquid crystal displays (LCDs) are non-self-emissive display devices, requiring a backlight module to provide a uniform surface light source for image display. Edge-lit backlight modules, with their advantages of thinness, light weight, and good light uniformity, are widely used in medium to large-sized LCD products such as televisions, monitors, and laptops. The light guide plate is the core optical component of the edge-lit backlight module, its function being to transform linear point light sources incident from the side into uniformly distributed surface light sources. Polymethyl methacrylate (PMMA) is currently the dominant material for light guide plate substrates due to its high visible light transmittance, excellent moldability, and moderate cost.

[0003] To achieve uniform light emission across the entire surface of the light guide plate, the industry commonly employs laser dotting technology to create a light scattering structure. This involves focusing a high-energy laser beam onto the surface of the light guide plate, forming micron-sized scattering dots through localized thermal ablation or melting modification. A gradient design, gradually increasing the dot density from the incident light side to the distal light side, compensates for the intensity attenuation of light propagating within the light guide plate, ultimately achieving a uniform in-plane distribution of emitted light brightness. This process features high processing precision, flexible pattern design, and high mass production efficiency, making it the mainstream manufacturing solution for large-size side-entry light guide plates.

[0004] However, the aforementioned laser dotting process suffers from unavoidable thermal stress defects, becoming a core bottleneck for the long-term reliability of the light guide plate. During laser dotting, a high-energy beam acts on the material surface for an extremely short time, causing the irradiated area to instantly rise to hundreds of degrees Celsius, resulting in rapid thermal expansion of the material surface. Meanwhile, the interior of the light guide plate is not directly irradiated by the laser, leading to a slower temperature rise and limited expansion. This creates a significant deformation difference between the surface and interior, resulting in an imbalance between instantaneous surface compressive stress and internal tensile stress. During the subsequent rapid cooling process, the surface material shrinks faster than the interior. Due to the high rigidity of PMMA molecular chains and their weak stress relaxation ability at room temperature, most of the internal stress cannot be completely released during cooling. Ultimately, it is frozen as residual stress in the area surrounding the dots, resulting in a non-uniform stress distribution of surface compressive stress and internal tensile stress.

[0005] During the actual service life of LCD screens, the backlight module is subjected to the heat generated by LED strips, the diurnal fluctuation of ambient temperature, and the alternating hot and cold cycles of power-on and power-off. The light guide plate repeatedly undergoes thermal expansion and contraction. The residual internal stress introduced by the laser dotting process accumulates, releases, and redistributes under thermal shock. When the accumulated stress exceeds the yield limit of the material, it will cause macroscopic warping deformation of the light guide plate. Warping of the light guide plate not only changes the assembly gap between it and the upper and lower optical films, causing local interference fringes and uneven brightness, but also changes the light emission angle and optical path distribution of the scattering dots, directly destroying the original brightness uniformity design. This results in display defects such as bright lines and dark corners, seriously reducing the image quality and lifespan of the LCD screen. It is a key technical problem restricting the yield and performance improvement of large-size, high-reliability edge-lit backlight modules.

[0006] To address the aforementioned issues, existing technologies often employ post-annealing of the substrate to eliminate internal stress. However, conventional annealing can only effectively release the overall residual stress generated during polymerization, and its effect on releasing localized or micro-area residual stress introduced by laser dotting is very limited. Some solutions use low-expansion materials such as polycarbonate (PC) and cyclic olefin polymers (COP) to replace PMMA. Although this can reduce the magnitude of thermal expansion, it suffers from drawbacks such as high material cost, difficult molding and processing, and the impact of birefringence on optical performance. Another solution improves the toughness of the material by blending flexible components, but problems such as easy migration and precipitation of blended components, poor long-term stability, and increased optical haze exist. It has always been impossible to effectively balance high light transmittance, high heat resistance, and stress relaxation ability. Summary of the Invention

[0007] To address the problem of stress warping in existing backlight module light guide plates, which affects light emission uniformity, this invention provides a liquid crystal display backlight module and its manufacturing method.

[0008] The technical solution adopted by the present invention to solve the above-mentioned technical problems is as follows: On one hand, the present invention provides a liquid crystal display backlight module, including a side-lit light source, a light guide plate, and a reflective layer. The side-lit light source is located on the side of the light guide plate and faces the light guide plate. The light guide plate has a light-emitting surface and a backlight surface. The reflective layer is located on the backlight surface of the light guide plate. The backlight surface of the light guide plate is provided with scattering points formed by laser dotting. The light guide plate is an acrylate crosslinked copolymer. The acrylate crosslinked copolymer includes an acrylate backbone and polyether segments. The acrylate backbone includes methyl methacrylate units, adamantane acrylate units, and siloxane acrylate units. The two ends of the polyether segments are covalently connected between different siloxane acrylate units.

[0009] Optionally, in the acrylate crosslinked copolymer, the mass ratio of methyl methacrylate units, adamantane acrylate units, siloxane acrylate units and polyether segments is (74~78):(13~15):(3~4):(4~6).

[0010] Optionally, the methyl methacrylate unit is a structural unit formed by the reaction of methyl methacrylate; and / or, The adamantane acrylate unit is a structural unit formed by the reaction of adamantane acrylate monomers, wherein the adamantane acrylate monomers include one or more of 1-adamantane acrylate, 1-adamantane methacrylate, 2-adamantane acrylate, and 3-hydroxy-1-adamantane methacrylate; and / or, The siloxane acrylate unit is a structural unit formed by the reaction of siloxane acrylate monomers, and the siloxane acrylate monomers include one or more of γ-methacryloyloxypropyltrimethoxysilane, γ-methacryloyloxypropyltriethoxysilane, vinyltrimethoxysilane, and vinyltriethoxysilane.

[0011] Optionally, the polyether segment is a bridging unit formed by the reaction of polyethylene glycol, and the number-average molecular weight of the polyethylene glycol is 300-450.

[0012] Optionally, the scattering point is a recessed point that extends inward from the backlight surface of the light guide plate, and the density of the scattering points on the backlight surface gradually increases along the direction away from the side-lit light source.

[0013] Optionally, the backlight module of the liquid crystal display screen further includes a diffusion layer, which is located on the light-emitting surface of the light guide plate.

[0014] In another aspect, the present invention provides a method for manufacturing a liquid crystal display backlight module as described above, comprising the following operations: (1) Pre-hydrolysis condensation reaction: Polyethylene glycol, siloxane acrylate monomer and deionized water are mixed, the pH of the system is adjusted to weak acidity, the temperature is raised and the reaction is stirred under nitrogen protection, so that the siloxane acrylate monomer is hydrolyzed and condensed with the terminal hydroxyl groups of polyethylene glycol to obtain a polyethylene glycol-silane macromolecular crosslinking agent with polymerizable double bonds at both ends. (2) Free radical prepolymerization: Add methyl methacrylate and adamantane acrylate monomers to the system obtained in step (1), stir evenly, add initiator and chain transfer agent, heat under nitrogen protection to carry out prepolymerization, stop the reaction when the viscosity of the system reaches 1000~1500mPa・s, and obtain prepolymer; (3) Casting polymerization and curing: After vacuum degassing, the prepolymer is injected into a flat mold, heated to remove the solvent and complete free radical copolymerization and siloxane condensation crosslinking to obtain an acrylate crosslinked copolymer substrate; (4) Substrate post-treatment and laser dotting: After the acrylate cross-linked copolymer substrate is demolded, it is annealed to eliminate the internal stress of polymerization. After cutting and side polishing, laser dotting is performed to prepare scattering points on one side of the substrate to obtain the light guide plate. (5) Backlight module assembly: The side-lit light source, reflective layer and light guide plate are assembled to obtain the backlight module of the liquid crystal display screen.

[0015] Optionally, in step (1), the pH value of the system is 4.0~5.0, the reaction temperature is 50~70℃, and the reaction time is 1.5~3h.

[0016] Optionally, in step (2), the initiator includes one or more of azobisisobutyronitrile, azobisisoheptanenitrile, benzoyl peroxide, and tert-butyl peroxypentanoate, and the chain transfer agent includes one or more of n-dodecyl mercaptan, tert-dodecyl mercaptan, n-octyl mercaptan, and mercaptoethanol.

[0017] Optionally, the annealing process involves placing the acrylate crosslinked copolymer substrate in an environment of 90~110℃ for 3 hours, and then cooling it to room temperature at a rate of ≤10℃ / h.

[0018] The backlight module of the liquid crystal display provided by the present invention uses an acrylate cross-linked copolymer as the light guide plate material. The acrylate cross-linked copolymer includes methyl methacrylate units, adamantane acrylate units, siloxane acrylate units, and polyether segments. Among them, the methyl methacrylate units provide basic high light transmittance and processing performance; the polyether segments have low rotation barriers within the COC ether bonds and remain in a highly elastic state throughout the service range of -40~85℃; during laser dotting, the surface layer experiences instantaneous high-temperature expansion, generating compressive stress, while the interior is subjected to tension, generating tensile stress. The polyether segments can buffer poor local deformation through rapid conformational stretching / coiling and slowly release stress during cooling, thereby reducing the residual stress in the dot area by more than 50%, which essentially alleviates the imbalance between surface compressive stress and internal tensile stress. The siloxane acrylate unit integrates into the main chain via double bond copolymerization and simultaneously achieves intermolecular crosslinking and covalent grafting with polyethylene glycol through hydrolysis and condensation. This ensures that the polyether segments do not migrate or precipitate, resulting in long-term stability far superior to physically blended systems. Furthermore, the mildly crosslinked network restricts permanent chain slippage, avoiding the side effect of increased high-temperature creep after introducing flexible chains. Meanwhile, the cage-like alicyclic structure of the adamantane acrylate unit generates strong steric hindrance, raising the material's glass transition temperature to above 120°C. This overcomes the problem of decreased glass transition temperature caused by polyether segments, while simultaneously compressing the molecular free volume, reducing the intrinsic linear thermal expansion coefficient by more than 30%, fundamentally reducing the driving force of thermal deformation. Attached Figure Description

[0019] Figure 1 This is a schematic diagram of the structure of the liquid crystal display backlight module provided by the present invention; Figure 2 This is a schematic diagram of the backlight scattering point distribution of the light guide plate provided by the present invention.

[0020] The reference numerals in the accompanying drawings are as follows: 1. Side-lit light source 1; 2. Light guide plate 2; 21. Scattering point 21; 3. Reflective layer 3; 4. Diffuse layer 4. Detailed Implementation

[0021] To make the technical problems solved, the technical solutions, and the beneficial effects of this invention clearer, the invention will be further described in detail below with reference to the accompanying drawings and embodiments. It should be understood that the specific embodiments described herein are merely illustrative of the invention and are not intended to limit the invention.

[0022] like Figure 1 and Figure 2 As shown, an embodiment of the present invention provides a liquid crystal display backlight module, including a side-lit light source 1, a light guide plate 2, and a reflective layer 3. The side-lit light source 1 is located on the side of the light guide plate 2 and faces the light guide plate 2. The light guide plate 2 has a light-emitting surface and a backlight surface. The reflective layer 3 is located on the backlight surface of the light guide plate 2. The backlight surface of the light guide plate 2 is provided with scattering points 21 formed by laser dotting. The light guide plate 2 is an acrylate crosslinked copolymer. The acrylate crosslinked copolymer includes an acrylate backbone and polyether segments. The acrylate backbone includes methyl methacrylate units, adamantane acrylate units, and siloxane acrylate units. The two ends of the polyether segments are covalently connected between different siloxane acrylate units.

[0023] The backlight module in this embodiment is a side-lit architecture. The side-lit light source 1 is a strip light panel equipped with multiple MiniLED chips, which can be set on one, two, or four sides of the light guide plate 2. The LED emitting surface faces the light-incident surface of the light guide plate 2, and the gap between the surfaces can be filled with high-refractive-index optical adhesive to improve coupling efficiency. The peak wavelength of the LED chip is 450~460nm, and white light output is achieved with phosphor. The light guide plate 2 is a homogeneous amorphous transparent plate with a thickness of 2~4mm. The light-emitting surface is an optically polished surface. The reflective layer 3 is a silver-plated reflective film on a PET substrate or a white PET foam reflective sheet with a reflectivity of ≥95%. It is attached to the outer side of the backlight surface of the light guide plate 2 to reflect leaked light back to the light guide plate 2 for recycling.

[0024] From a microscopic perspective, the acrylate backbone is a carbon chain polymer formed by the free radical polymerization of methyl methacrylate units, adamantane acrylate units, and siloxane acrylate units. Methyl ester groups, adamantane ester groups, and siloxane-containing side groups are suspended on the backbone. The polyether segments are bridge chains formed by the condensation reaction of polyethylene glycol with hydroxyl groups at both ends. The two ends are connected to the siloxane side groups of two different backbones by Si-OC covalent bonds, forming a three-dimensional cross-linked network composed of rigid backbones and flexible bridge chains. The system has a homogeneous and transparent structure with no macroscopic phase separation and no characteristic absorption peaks in the visible light band.

[0025] The methyl methacrylate unit provides fundamental high light transmittance and processing performance; the polyether segments have low rotational barriers within the COC ether bonds, maintaining a highly elastic state throughout the service range of -40 to 85°C; during laser dotting, the surface experiences instantaneous high-temperature expansion generating compressive stress, while the interior experiences tensile stress. The polyether segments can buffer poor local deformation through rapid conformational stretching / coiling, and slowly release stress during cooling, reducing residual stress in the dotted area by more than 50%, fundamentally alleviating the imbalance between surface compressive stress and internal tensile stress. The siloxane acrylate unit is integrated into the main chain through double bond copolymerization and simultaneously achieves intermolecular crosslinking and covalent grafting with polyethylene glycol through hydrolysis and condensation. This ensures that the polyether segments do not migrate or precipitate, resulting in long-term stability far superior to physically blended systems; it also restricts permanent chain slippage through a mildly crosslinked network, avoiding the side effect of increased high-temperature creep after introducing flexible chains. The cage-like alicyclic structure of the adamantane acrylate unit generates strong steric hindrance, raising the glass transition temperature of the material to over 120°C. This overcomes the problem of the glass transition temperature decreasing due to the polyether segments. At the same time, it compresses the free volume of molecules, reducing the intrinsic linear thermal expansion coefficient by more than 30%, thereby reducing the driving force of thermal deformation from the root.

[0026] In an optional implementation, the side-lit light source 1 can use a cold cathode fluorescent lamp instead of an LED light strip, which is suitable for traditional large-size backlighting scenarios; the reflective layer 3 can be formed directly on the backlight surface of the light guide plate 2 with a structure coated with a high-reflectivity titanium dioxide coating, eliminating the need for an independent reflective sheet and further reducing the module thickness; some methyl methacrylate units in the acrylate main chain can be replaced with ethyl methacrylate units to fine-tune the material's toughness and processability without affecting the core anti-warping function.

[0027] In some embodiments, the mass ratio of methyl methacrylate units, adamantane acrylate units, siloxane acrylate units and polyether segments in the acrylate crosslinked copolymer is (74~78):(13~15):(3~4):(4~6).

[0028] The above mass ratios are based on the total dry basis mass of the monomers and functional components participating in the reaction, corresponding to the mass ratio of methyl methacrylate, adamantane acrylate, siloxane acrylate monomers to polyethylene glycol at the time of feeding, and the mass loss of small molecule condensation products can be ignored. The specific ratio values ​​within this range include, but are not limited to: (74:13:3:4), (74:13:3:5), (74:13:3:6), (74:14:3:4), (74:14:3.5:5), (74:15:4:6), (75:13:3:4), (75:14:3.5:5), (75:15:4:6), (76:13:3:5), (76:14:3:5), (76:15:3.5:5), (77:13:3:6), (77:14:4:4), (77:15:3.5:5), (78:13:3:4), (78:14:3.5:5), (78:15:4:6).

[0029] For methyl methacrylate units, when their proportion is less than 74 parts, the proportion of matrix resin is insufficient, the optical uniformity of the material decreases, and the proportion of high-cost monomers increases, resulting in poor economic efficiency. When their proportion is greater than 78 parts, the proportion of rigid monomers and flexible units is diluted, the glass transition temperature increases by less than 10°C, the stress relaxation effect is weak, and the warping problem cannot be effectively improved.

[0030] For adamantane acrylate unit, when its proportion is less than 13 parts, the rigidity of the main chain is not sufficiently improved, which cannot offset the decrease in heat resistance caused by the polyether segment. The glass transition temperature of the material is lower than 120℃, and the high-temperature creep resistance is not up to standard. When its proportion is higher than 15 parts, the brittleness of the material increases significantly, the chipping rate during cutting increases, and the melt fluidity decreases, making it easy for poor filling to occur during casting.

[0031] For siloxane acrylate units, when their proportion is less than 3 parts, the crosslinking point density is insufficient, the polyethylene glycol grafting rate is less than 60%, and a large amount of ungrafted polyethylene glycol is prone to migration and precipitation, resulting in crystallization on the surface after long-term use. When their proportion is more than 4 parts, the tendency of silane self-polymerization increases, forming nano-sized polysiloxane particles, which leads to a material haze greater than 1% and a light transmittance reduced to below 90%, affecting the light guiding efficiency.

[0032] For polyether segments, when their proportion is less than 4 parts, the number of flexible segments is insufficient, the residual stress decreases only slightly after laser dotting, and the improvement of thermal shock warping is not obvious; when their proportion is more than 6 parts, the glass transition temperature of the material drops below 120℃, and permanent deformation is likely to occur after long-term use at 80℃, and the surface pencil hardness and scratch resistance decrease.

[0033] In some embodiments, the methyl methacrylate unit is a structural unit formed by the reaction of methyl methacrylate.

[0034] Methyl methacrylate units are structural units formed by the free radical addition polymerization of methyl methacrylate monomers, after the double bonds are opened. They constitute the main body of the copolymer backbone and can provide more than 92% visible light transmittance, excellent weather resistance and molding processability. They are the basic carrier of the optical properties of copolymers.

[0035] In some embodiments, the adamantane acrylate unit is a structural unit formed by the reaction of adamantane acrylate monomers, and the adamantane acrylate monomers include one or more of 1-adamantane acrylate, 1-adamantane methacrylate, 2-adamantane acrylate, and 3-hydroxy-1-adamantane methacrylate.

[0036] The adamantane acrylate unit is a side group unit formed by the polymerization of acrylate monomers containing an adamantane cage-like skeleton. The adamantane is a saturated alicyclic structure of tricyclic decane, exhibiting extremely high rigidity and no conjugated structure. 1-Adamantane methacrylate is preferred, as its polymerization reactivity ratio is close to that of methyl methacrylate, resulting in optimal copolymerization uniformity. The working principle of the adamantane acrylate unit lies in the steric hindrance effect generated by the large-volume cage-like side group, which significantly increases the rotational barrier within the main chain, thereby raising the glass transition temperature. Simultaneously, the dense molecular packing compresses the free volume, reducing the intrinsic coefficient of thermal expansion of the material.

[0037] In some embodiments, the siloxane acrylate unit is a structural unit formed by the reaction of siloxane acrylate monomers, and the siloxane acrylate monomers include one or more of γ-methacryloyloxypropyltrimethoxysilane, γ-methacryloyloxypropyltriethoxysilane, vinyltrimethoxysilane, and vinyltriethoxysilane.

[0038] The siloxane acrylate unit is a silane coupling agent containing both polymerizable carbon-carbon double bonds and hydrolyzable siloxane groups. It is a structural unit that integrates into the main chain via double bond polymerization and forms crosslinking points via silanol condensation. This unit performs three functions: first, it integrates into the polymer main chain through double bond copolymerization, achieving molecular-level bonding; second, it forms intermolecular crosslinking nodes through silanol self-condensation; and third, it provides covalent grafting sites for flexible bridging chains through condensation with polyethylene glycol hydroxyl groups.

[0039] In some embodiments, the polyether segment is a bridging unit formed by the reaction of polyethylene glycol, and the number-average molecular weight of the polyethylene glycol is 300-450.

[0040] The polyether segment is a flexible bridging structure formed by the condensation of the hydroxyl groups at both ends of polyethylene glycol with siloxane units, with -O-CH2CH2- as the repeating unit. The two ends are covalently connected between different siloxane units through Si-OC bonds.

[0041] When the number-average molecular weight is below 300, the polyether chain segments are too short, resulting in insufficient freedom of chain movement, poor stress relaxation, and weak instantaneous stress buffering capacity during laser atomization. Furthermore, the excessive number of bridging points per unit mass increases the system's rigidity. When the number-average molecular weight is above 450, the polyether chain segments are too long, increasing the difference in solubility parameters between the polyether and acrylate matrix, making microphase separation more likely. This leads to increased material haze and decreased light transmittance; moreover, increased long-chain entanglement increases the tendency for high-temperature creep.

[0042] The number-average molecular weight of polyethylene glycol was determined by gel permeation chromatography under the following conditions: tetrahydrofuran as the mobile phase, narrow-distribution polystyrene as the standard, column temperature 35℃, flow rate 1.0 mL / min, and differential refractive index detector.

[0043] like Figure 2 As shown, in some embodiments, the scattering point 21 is a concave point recessed inward from the backlight surface of the light guide plate 2, and the density of the scattering points 21 on the backlight surface gradually increases along the direction away from the side-lit light source 1.

[0044] Scattering point 21 is an inwardly recessed pit formed by laser thermal ablation or melt modification. The cross-section is hemispherical with a diameter of 10~50μm and a depth of 2~10μm. There is a 1~3μm thick melt-re-solidification modification zone around the pit, with a refractive index slightly lower than that of the matrix.

[0045] The principle of this density gradient design is that light propagates in the light guide plate 2 in the form of total internal reflection, and gradually attenuates due to absorption and end-face loss as the propagation distance increases; by increasing the density of scattering points 21 by gradient, the probability of light coupling and emission from the far side is increased, which can compensate for the light intensity attenuation and improve the uniformity of light output across the entire plate.

[0046] In some embodiments, the liquid crystal display backlight module further includes a diffusion layer 4, which is located on the light-emitting surface of the light guide plate 2.

[0047] The substrate of the diffusion layer 4 is an optical-grade PET film with a thickness of 100~200μm, and the surface is coated with an acrylic coating containing diffusion particles. The diffusion particles are PMMA microspheres or silica microspheres with a particle size of 2~10μm. The coating haze is 50%~80%, and the total light transmittance is ≥90%. The function of the diffusion layer 4 is to homogenize the light emitted from the light guide plate 2, cover the graininess of the scattering points 21, and eliminate the visibility of the dots; at the same time, it expands the light emission angle and improves the side-view brightness attenuation.

[0048] In other optional embodiments, a lower brightness enhancement film, an upper brightness enhancement film, and a reflective polarizer can be sequentially stacked on the light-emitting side of the light guide plate 2; wherein the brightness enhancement film is a prism structure with a prism apex angle of 90°, which can refract large-angle light back to the normal direction, thereby improving the brightness of the front side; the reflective polarizer can reflect useless polarized light back to the light guide plate 2 for recycling. In a further optional embodiment, an integrated diffusion light guide plate 2 structure can be adopted, that is, the diffusion microstructure is directly formed on the light-emitting surface of the light guide plate 2, eliminating the need for a separate diffusion layer 4.

[0049] Another embodiment of the present invention provides a method for manufacturing a liquid crystal display backlight module as described above, comprising the following operations: (1) Pre-hydrolysis condensation reaction: Polyethylene glycol, siloxane acrylate monomer and deionized water are mixed, the pH of the system is adjusted to weak acidity, the temperature is raised and the reaction is stirred under nitrogen protection, so that the siloxane acrylate monomer is hydrolyzed and condensed with the terminal hydroxyl groups of polyethylene glycol to obtain a polyethylene glycol-silane macromolecular crosslinking agent with polymerizable double bonds at both ends. (2) Free radical prepolymerization: Add methyl methacrylate and adamantane acrylate monomers to the system obtained in step (1), stir evenly, add initiator and chain transfer agent, heat under nitrogen protection to carry out prepolymerization, stop the reaction when the viscosity of the system reaches 1000~1500mPa・s, and obtain prepolymer; (3) Casting polymerization and curing: After vacuum degassing, the prepolymer is injected into a flat mold, heated to remove the solvent and complete free radical copolymerization and siloxane condensation crosslinking to obtain an acrylate crosslinked copolymer substrate; (4) Substrate post-processing and laser dotting: After the acrylate cross-linked copolymer substrate is demolded, it is annealed to eliminate the internal stress of polymerization. After cutting and side polishing, laser dotting is performed to prepare scattering points 21 on one side of the substrate to obtain the light guide plate 2. (5) Backlight module assembly: The side-lit light source 1, the reflective layer 3, and the light guide plate 2 are assembled to obtain the backlight module of the liquid crystal display screen.

[0050] In some embodiments, in step (1), the pH value of the system is 4.0~5.0, the reaction temperature is 50~70℃, and the reaction time is 1.5~3h.

[0051] Specific values ​​within the above parameter range include, but are not limited to: pH values ​​of 4.0, 4.1, 4.2, 4.3, 4.4, 4.5, 4.6, 4.7, 4.8, 4.9, and 5.0; reaction temperatures of 50℃, 55℃, 60℃, 65℃, and 70℃; and reaction times of 1.5h, 2.0h, 2.5h, and 3.0h.

[0052] Glacial acetic acid is the preferred pH adjuster due to its mild acidity, volatility, and lack of residue; dilute hydrochloric acid, citric acid, and other weak acids can also be used. The reaction process can be monitored using Fourier transform infrared spectroscopy, focusing on the characteristic peak of the Si-OC bond (approximately 1100 cm⁻¹). -1 The intensity change can be used to determine the progress of the grafting reaction.

[0053] In some embodiments, in step (2), the initiator includes one or more of azobisisobutyronitrile, azobisisoheptanenitrile, benzoyl peroxide, and tert-butyl peroxypentanoate, and the chain transfer agent includes one or more of n-dodecyl mercaptan, tert-dodecyl mercaptan, n-octyl mercaptan, and mercaptoethanol.

[0054] Initiators are used to generate free radicals through homolytic cracking upon heating, which initiate the addition polymerization of acrylate double bonds, serving as the source of active centers for the polymerization reaction.

[0055] Chain transfer agents are used to react with growing free radicals to terminate the current growing chain and generate new active free radicals. This allows for the control of polymer molecular weight and distribution without changing the polymerization rate, thus avoiding the gel effect in the later stages of polymerization.

[0056] In some embodiments, the annealing process is as follows: the acrylate crosslinked copolymer substrate is kept at 90~110°C for 3 hours, and then cooled to room temperature at a rate of ≤10°C / h.

[0057] The present invention will be further described below through specific embodiments: Example 1 This embodiment illustrates the method for preparing the light guide plate of the liquid crystal display backlight module disclosed in this invention, including the following operations: Step 1, Pre-hydrolysis condensation reaction: Add 5 parts by mass of polyethylene glycol with a number average molecular weight of 400, 3.5 parts by mass of γ-methacryloyloxypropyltrimethoxysilane, and 0.25 parts by mass of deionized water to a sealed reactor equipped with a stirrer, a condenser, and a nitrogen gas interface. Add glacial acetic acid to adjust the pH of the system to 4.5, start stirring, and control the speed at 180 rpm. After purging the air in the reactor with nitrogen for 15 minutes, raise the temperature to 60°C, keep it at this temperature and stir for 2 hours to hydrolyze the silane and condense it with the terminal hydroxyl groups of polyethylene glycol to obtain a polyethylene glycol-silane macromolecular crosslinking agent with polymerizable double bonds at both ends.

[0058] Step 2, Free radical prepolymerization: Add 76 parts by mass of methyl methacrylate and 14 parts by mass of 1-adamantane methacrylate to the system obtained in Step 1, and stir for 20 min until the system is homogeneous; purge with nitrogen again for 10 min, add 0.11 parts by mass of azobisisobutyronitrile and 0.08 parts by mass of n-dodecyl mercaptan, stir to dissolve, heat to 72℃, stir at low speed, control the speed at 120 rpm, and monitor the viscosity of the system in real time using a rotational viscometer. When the viscosity reaches 1200 mPa·s, immediately introduce cooling water to terminate the reaction and obtain the prepolymer.

[0059] Step 3, Casting Polymerization and Curing: After cooling the prepolymer to 25°C, transfer it to a vacuum degassing kettle and degas for 9 minutes under a vacuum of -0.098MPa. Stablely pour it into a flat mold composed of two pieces of ultra-white tempered glass and PVC sealing strips, with the thickness of the sealing strips controlled to a substrate thickness of 3mm. After sealing, place it horizontally in a hot air circulating oven and use a segmented gradient heating process: constant temperature polymerization at 60°C for 12 hours, heating to 85°C for 4 hours, and heating to 110°C for 2 hours to complete free radical copolymerization and siloxane condensation crosslinking.

[0060] Step 4, Substrate Annealing: After polymerization, slowly cool down to below 50°C at a rate of 8°C / h to demold; place the substrate horizontally in a hot air circulating oven and anneal at 100°C for 3 hours, then cool down to room temperature at a rate of 8°C / h to obtain the acrylate crosslinked copolymer substrate.

[0061] Step 5, Laser Dotting and Module Assembly: The substrate is cut to the specified test size, and the sides are polished to a roughness Ra≤0.2μm. Then, a 355nm ultraviolet laser is used to perform gradient dotting on the back surface of the substrate; the average diameter of the scattered dots is about 30μm, and the density on the incident side is 8 dots / mm. 2 High beam density 40 pixels / mm 2 The light guide plate is obtained.

[0062] Example 2 This embodiment illustrates the method for preparing the light guide plate of the liquid crystal display backlight module disclosed in this invention, including most of the operational steps in Embodiment 1, with the following differences: In step 1, the amount of polyethylene glycol added is 4 parts by mass, the amount of γ-methacryloyloxypropyltrimethoxysilane added is 3 parts by mass, the amount of deionized water is 0.20 parts by mass, and the amount of glacial acetic acid is 0.07 parts by mass. In step 2, the amount of methyl methacrylate added is 78 parts by mass, the amount of 1-adamantane methacrylate added is 13 parts by mass, the amount of azobisisobutyronitrile added is 0.10 parts by mass, and the amount of n-dodecyl mercaptan added is 0.07 parts by mass.

[0063] Example 3 This embodiment illustrates the method for preparing the light guide plate of the liquid crystal display backlight module disclosed in this invention, including most of the operational steps in Embodiment 1, with the following differences: In step 1, the amount of polyethylene glycol added is 6 parts by mass, the amount of γ-methacryloyloxypropyltrimethoxysilane added is 4 parts by mass, the amount of deionized water is 0.30 parts by mass, and the amount of glacial acetic acid is 0.09 parts by mass. In step 2, the amount of methyl methacrylate added is 74 parts by mass, the amount of 1-adamantane methacrylate added is 15 parts by mass, the amount of azobisisobutyronitrile added is 0.12 parts by mass, and the amount of n-dodecyl mercaptan added is 0.09 parts by mass.

[0064] Example 4 This embodiment illustrates the method for preparing the light guide plate of the liquid crystal display backlight module disclosed in this invention, including most of the operational steps in Embodiment 1, with the following differences: In step 1, polyethylene glycol with a number average molecular weight of 300 is used instead of polyethylene glycol with a number average molecular weight of 400, and the amount added remains unchanged.

[0065] Example 5 This embodiment illustrates the method for preparing the light guide plate of the liquid crystal display backlight module disclosed in this invention, including most of the operational steps in Embodiment 1, with the following differences: In step 1, γ-methacryloxypropyltriethoxysilane is used instead of γ-methacryloxypropyltrimethoxysilane, while the amount added remains unchanged.

[0066] Comparative Example 1 This comparative example is used to illustrate the method for preparing the light guide plate of the liquid crystal display backlight module disclosed in this invention. It includes most of the operation steps in Example 1, but the difference is: Without performing the pre-hydrolysis condensation reaction in step 1, 100 parts by mass of methyl methacrylate are directly mixed with an initiator and a chain transfer agent, followed by prepolymerization and casting curing. No 1-adamantane methacrylate, silane monomer, or polyethylene glycol is added to obtain a pure PMMA substrate.

[0067] Comparative Example 2 This comparative example is used to illustrate the method for preparing the light guide plate of the liquid crystal display backlight module disclosed in this invention. It includes most of the operation steps in Example 1, but the difference is: In step 1, polyethylene glycol is not added; only 4.5 parts by weight of γ-methacryloyloxypropyltrimethoxysilane are added for hydrolysis. In step 2, the amount of methyl methacrylate added is 79 parts by weight, and the amount of 1-adamantane methacrylate added is 14 parts by weight.

[0068] Comparative Example 3 This comparative example is used to illustrate the method for preparing the light guide plate of the liquid crystal display backlight module disclosed in this invention. It includes most of the operation steps in Example 1, but the difference is: In step 2, 1-adamantane methacrylate is not added, and the amount of methyl methacrylate added is 90 parts by weight.

[0069] Comparative Example 4 This comparative example is used to illustrate the method for preparing the light guide plate of the liquid crystal display backlight module disclosed in this invention. It includes most of the operation steps in Example 1, but the difference is: Without performing the pre-hydrolysis condensation reaction in step 1, and without adding γ-methacryloyloxypropyltrimethoxysilane, 76 parts by mass of methyl methacrylate, 14 parts by mass of 1-adamantane methacrylate, and 5 parts by mass of polyethylene glycol with a number average molecular weight of 400 are directly mixed evenly, and then an initiator and chain transfer agent are added for prepolymerization and casting curing. The polyethylene glycol is dispersed in the matrix in the form of physical blending.

[0070] Comparative Example 5 This comparative example is used to illustrate the method for preparing the light guide plate of the liquid crystal display backlight module disclosed in this invention. It includes most of the operation steps in Example 1, but the difference is: In step 1, the amount of polyethylene glycol added is 10 parts by weight; In step 2, the amount of methyl methacrylate added is 71 parts by weight.

[0071] Performance testing The light guide plate samples prepared above were subjected to the following performance tests: Glass transition temperature (Tg): Tested using a dynamic thermomechanical analyzer (DMA) in single cantilever beam mode, frequency 1Hz, heating rate 3℃ / min, temperature range 30~160℃, and the temperature corresponding to the peak value of tanδ is taken as Tg, in ℃.

[0072] Residual stress at laser-marked dots: The residual stress value of the center area of ​​the dots was calculated by converting the birefringence path difference into MPa and taking the average value of 5 test points.

[0073] Thermal shock warpage: A 55-inch light guide plate sample was placed in a high and low temperature shock test chamber and cycled 100 times from -40℃ to 85℃, with each temperature zone lasting 30 minutes and a temperature zone transition time of ≤10 seconds. After the cycle, the maximum warpage height of the plate surface was measured using a coordinate measuring machine, in mm.

[0074] The performance test results are shown in Table 1.

[0075] Table 1 The test results in Table 1 show that: The light guide plates prepared in Examples 1-5 of this invention all maintain a glass transition temperature above 122°C, and the residual stress after laser dotting is reduced to below 2.5 MPa. The warpage after 100 thermal shocks is ≤0.3 mm. While ensuring the heat resistance of the substrate, the imbalance between surface compressive stress and internal tensile stress caused by laser dotting is effectively alleviated, significantly improving the light guide plate's resistance to thermal shock warping and solving the core defect of easy warping of laser dotted light guide plates in the prior art.

[0076] Comparing Example 1 and Comparative Example 2, it can be seen that after introducing covalently bridged polyethylene glycol segments, the residual stress at the dots decreased from 4.6 MPa to 2.1 MPa, and the thermal shock warpage decreased from 0.71 mm to 0.25 mm. This indicates that the flexible polyethylene glycol bridge can effectively buffer the stress difference between the surface and the interior generated by laser dotting through conformational adjustment, significantly improving the stress relaxation ability, which is the core factor in improving warpage.

[0077] Comparing Example 1 and Comparative Example 3, it can be seen that when the rigid unit of adamantane acrylate is missing, the glass transition temperature of the material is only 109°C. Although the residual stress is low, the heat resistance of the matrix is ​​insufficient and the intrinsic thermal deformation driving force is large. The warpage after thermal shock is still 0.84 mm. The cage-like rigid structure of adamantane acrylate can increase the glass transition temperature of the matrix and offset the decrease in heat resistance caused by the polyether segments. The two work together to achieve a balance between heat resistance and stress relaxation ability.

[0078] Comparing Example 1 and Comparative Example 4, it can be seen that without the addition of silane monomers, polyethylene glycol is dispersed in the matrix only in a physical blending form, and cannot bridge different molecular chain segments through covalent bonds. On the one hand, it is difficult to form a continuous and stable stress transfer network, and the stress relaxation effect is greatly reduced, with the residual stress at the dot increasing to 3.8 MPa. On the other hand, the matrix lacks cross-linking constraints, resulting in a decrease in high-temperature creep resistance, a reduction in glass transition temperature, and ultimately a thermal shock warpage of 0.76 mm. This proves that the silane-mediated covalent bridging structure is the key structural basis for ensuring the long-term stress relaxation effect of polyethylene glycol and improving its anti-warpage performance.

[0079] Comparing Example 1 and Comparative Example 5, it can be seen that when the amount of polyethylene glycol added exceeds the range defined by the present invention, the glass transition temperature of the material drops to 112°C, and the heat resistance and creep resistance of the matrix decrease significantly. Although the residual stress value is low, the permanent deformation under thermal shock increases, and the warpage rebounds. This proves that the component ratio range defined by the present invention is the optimal range for achieving performance balance.

[0080] After changing the molecular weight of polyethylene glycol in Example 4 and the type of silane monomer in Example 5, all properties remained at an excellent level, indicating that the technical solution of the present invention can be applied to a variety of raw materials of the same type, and the scope of protection has sufficient universality.

[0081] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, and improvements made within the spirit and principles of the present invention should be included within the protection scope of the present invention.

Claims

1. A liquid crystal display backlight module, characterized in that, The light guide includes a side-lit light source, a light guide plate, and a reflective layer. The side-lit light source is located on the side of the light guide plate and faces the light guide plate. The light guide plate has a light-emitting surface and a backlight surface. The reflective layer is located on the backlight surface of the light guide plate. The backlight surface of the light guide plate is provided with scattering points formed by laser dotting. The light guide plate is an acrylate crosslinked copolymer. The acrylate crosslinked copolymer includes an acrylate backbone and polyether segments. The acrylate backbone includes methyl methacrylate units, adamantane acrylate units, and siloxane acrylate units. The two ends of the polyether segments are covalently connected between different siloxane acrylate units.

2. The liquid crystal display backlight module according to claim 1, characterized in that, In the acrylate crosslinked copolymer, the mass ratio of methyl methacrylate unit, adamantane acrylate unit, siloxane acrylate unit and polyether segment is (74~78):(13~15):(3~4):(4~6).

3. The liquid crystal display backlight module according to claim 1, characterized in that, The methyl methacrylate unit is a structural unit formed by the reaction of methyl methacrylate; and / or, The adamantane acrylate unit is a structural unit formed by the reaction of adamantane acrylate monomers, wherein the adamantane acrylate monomers include one or more of 1-adamantane acrylate, 1-adamantane methacrylate, 2-adamantane acrylate, and 3-hydroxy-1-adamantane methacrylate; and / or, The siloxane acrylate unit is a structural unit formed by the reaction of siloxane acrylate monomers, and the siloxane acrylate monomers include one or more of γ-methacryloyloxypropyltrimethoxysilane, γ-methacryloyloxypropyltriethoxysilane, vinyltrimethoxysilane, and vinyltriethoxysilane.

4. The liquid crystal display backlight module according to claim 1, characterized in that, The polyether segment is a bridging unit formed by the reaction of polyethylene glycol, and the number-average molecular weight of the polyethylene glycol is 300-450.

5. The liquid crystal display backlight module according to claim 1, characterized in that, The scattering point is a recessed point that extends inward from the backlight surface of the light guide plate. The density of the scattering points on the backlight surface gradually increases along the direction away from the side-lit light source.

6. The liquid crystal display backlight module according to claim 1, characterized in that, The backlight module of the liquid crystal display screen also includes a diffusion layer, which is located on the light-emitting surface of the light guide plate.

7. The method for manufacturing a liquid crystal display backlight module as described in any one of claims 1 to 6, characterized in that, Includes the following operations: (1) Pre-hydrolysis condensation reaction: Polyethylene glycol, siloxane acrylate monomer and deionized water are mixed, the pH of the system is adjusted to weak acidity, the temperature is raised and the reaction is stirred under nitrogen protection, so that the siloxane acrylate monomer is hydrolyzed and condensed with the terminal hydroxyl groups of polyethylene glycol to obtain a polyethylene glycol-silane macromolecular crosslinking agent with polymerizable double bonds at both ends. (2) Free radical prepolymerization: Add methyl methacrylate and adamantane acrylate monomers to the system obtained in step (1), stir evenly, add initiator and chain transfer agent, heat under nitrogen protection to carry out prepolymerization, stop the reaction when the viscosity of the system reaches 1000~1500mPa・s, and obtain prepolymer; (3) Casting polymerization and curing: After vacuum degassing, the prepolymer is injected into a flat mold, heated to remove the solvent and complete free radical copolymerization and siloxane condensation crosslinking to obtain an acrylate crosslinked copolymer substrate; (4) Substrate post-treatment and laser dotting: After the acrylate cross-linked copolymer substrate is demolded, it is annealed to eliminate the internal stress of polymerization. After cutting and side polishing, laser dotting is performed to prepare scattering points on one side of the substrate to obtain the light guide plate. (5) Backlight module assembly: The side-lit light source, reflective layer and light guide plate are assembled to obtain the backlight module of the liquid crystal display screen.

8. The method for manufacturing a liquid crystal display backlight module according to claim 7, characterized in that, In step (1), the pH value of the system is 4.0~5.0, the reaction temperature is 50~70℃, and the reaction time is 1.5~3h.

9. The method for manufacturing a liquid crystal display backlight module according to claim 7, characterized in that, In step (2), the initiator includes one or more of azobisisobutyronitrile, azobisisoheptanenitrile, benzoyl peroxide, and tert-butyl peroxypentanoate, and the chain transfer agent includes one or more of n-dodecyl mercaptan, tert-dodecyl mercaptan, n-octyl mercaptan, and mercaptoethanol.

10. The method for manufacturing a liquid crystal display backlight module according to claim 7, characterized in that, The annealing process is as follows: the acrylate crosslinked copolymer substrate is placed in an environment of 90~110℃ and kept at that temperature for 3 hours, and then cooled to room temperature at a rate of ≤10℃ / h.